George Washington and the birth of our nation - Meltzer, Milton, 1915- (New York : F. Watts, 1986)
A biography of our first President, from his growing-up years in Virginia to his death at Mount Vernon.
Includes index.
Bibliography: p. 177-179.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
8.5
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Washington, George, -- 1732-1799.; Washington, George, -- 1732-1799.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- Politics and government -- 1783-1809 -- Juvenile literature